The Stability of Aggregates in Different Amazonian Agroecosystems Is Influenced by the Texture, Acidity, and Availability of Ca and Mg in the Soil - Alan Ferreira Leite de Lima; Milton César Costa Campos; Joalison de Brito Silva; Witória de Oliveira Araújo; Bruno Campos Mantovanelli; Fernando Gomes de Souza; Raphael Moreira Beirigo; Douglas Marcelo Pinheiro da Silva; Rodrigo Santana Macedo; Flávio Pereira de Oliveira (Agronomy, 2024)
The processes of occupation and exploitation in the Amazon have been increasing, and as a consequence, forest areas are being replaced by agroecosystems. As a consequence of this change, changes have been occurring in the soil attributes, and consequently, in the stability of aggregates in these environments. Thus, this work had two objectives: the first was to evaluate the impacts generated by the conversion of forests into agroecosystems on the soil attributes that are related to aggregates, in the southwestern region of the Amazon; the second objective was to evaluate the roles of pedophysical and pedochemical parameters on the stability of soil aggregates. The study was carried out on rural properties located in the southern part of Amazonas State, Brazil. Eight areas under different agroecosystems were selected: in the municipality of Canutama: (i) annatto, (ii) guarana, and (iii) cupuassu; in the municipality of Humaitá: (iv) cassava, (v) agroforestry, and (vi) sugarcane; and in the municipality of Manicoré: (vii) pasture and (viii) native forest. Unformed soil samples were collected from the 0.00–0.10 m layer and analyzed for aggregate stability, bulk density, soil organic carbon, and soil organic carbon stock. Univariate, bivariate, and multivariate analyses were performed. The largest soil aggregations occurred in the annatto, guarana, sugarcane, and pasture agroecosystems. We associate the greater aggregation capacity of soils with factors that are inherent to the cultivated species and soil properties. The first factor corresponds to the adaptability of the Amazonian and grass species and their ability to produce biomass. The second factor is related to the physical and chemical properties of Amazonian soils, largely influenced by the sand fraction, soil organic carbon, soil acidity, and availability of exchangeable Ca and Mg.